The Importance of Driving Thai Small and Medium Enterprises from an Exporter to Multinational Enterprise - Uthairat, Netchanock; Nami, Mariem; Sukato, Nuntasaree (Journal of Management Science Nakhon Pathom Rajabhat University, 2024)
Thai small and medium-sized enterprises (SMEs) play a significant role in the country's economy, a large portion of employment and economic output. However, many Thai SMEs operate only within the domestic market or a sole exporter of contract manufacturing. This limits their potential for growth and competitiveness. Pushing Thai SMEs from being purely exporters to becoming multinational enterprises (MNEs) can have a number of benefits for the businesses themselves, as well as for the Thai economy as a whole. MNEs have the potential to access larger markets, achieve economies of scale, and benefit from increased knowledge transfer and technological innovation. In order to support the transition of Thai SMEs from exporters to MNEs, it will be important to address the various barriers and challenges that they face. This may include providing access to finance, improving the business environment, and building the necessary infrastructure and support systems. The industries of Thai small and medium enterprises which should be support to multinational corporations should have the international competitive potential, the expanding market potential and the growth potential. Article history: Received 4 October 2023 Revised 8 November 2023 Accepted 10 November 2023 SIMILARITY INDEX = 0.00 %